PENGARUH SPIRONOLAKTON SEBAGAI TERAPI TAMBAHAN ACE INHIBITOR DAN/ATAU ANGIOTENSIN RECEPTOR BLOCKERS TERHADAP ALBUMINURIA PADA PENYAKIT GINJAL KRONIK PRADIALITIK STUDI KLINIS ACAK TERKONTROL BUTA GANDA - -, Yuriawantini; Suwitra, Ketu; Raka Widiana, I Gde; Sidharta Loekman, Jodi; Sudhan, Wayan; Kandarini, Yenny (journal of internal medicine, 2012)
Recently studies suggest that aldosterone contributes to progressive kidney disease. This has raised the possibility of using aldosterone antagonist in CKD. To evaluate effects of spironolactone 25 mg/day on albuminuria in CKD patients, thirty CKD patients were enrolled in randomized double blind placebo controlled study. Permutted block randomization was done to receive spironolactone 25 mg/day or placebo as control in addition to ACE inhibitors and/or ARBs. Albuminuria and blood pressure were examined at baseline and 12 weeks. Albuminuria was measured as urinary albumin:creatinine ration and compared as primary out come. During this study 15 patient were received conventional therapy and spironolactone 25 mg/day and 15 patient were received placebo. One of patient dropped-out after 4 weeks due to hiperkalemia in spironolactone group and one of patient in the control group lost to follow-up. After 12 weeks of therapy, in spironolactone group albuminuria was decreased from 510 (180.0 ? 798.0) to 254.0 (40.3 ? 491.8) mg/g, MD, 187.0 (29.0 ? 332.3) mg/g, p= 0.035 and in control group from 804.0 (52.0 ? 1126.0) to 637.0 (99.0 ? 1098.8) mg/g MD -10.5 (-186.5-86.0) mg/g, p= 0.490. There was significant difference of decreament of albuminuria in both groups (Z=-0.69, p=0.046). There were no statistically different of serum potassium levels and blood pressure in both groups after treatment. Baseline aldosterone levels were not significantly correlated with albuminuria (r = -0.128, p = 0.499). As Conclusion in this study is spironolactone reduces albuminuria in pradialytic CKD patients
Keywords: Albuminuria, spironolactone, CKD pradialysis, ACE inhibitors, ARBs